Reflections on Immediatism and Aesthetics - Cirone, Victor (eTopia, 2016)
This paper considers the aesthetic and political implications of Hakim Bey’s (also known as Peter Lamborn Wilson) Immediatist project. The paper begins with a discussion of the cosmogonic notions of Chaos and nothing that Bey adopts in his work and explores the ways in which these notions are foundational to his concept of Ontological Anarchy. It is then explained how, through indiscriminately drawing on a variety of mystical and magical traditions (from those of Pagan Greece and Ancient India to the contemporary Western Occult world) Immediatism aims to establish an experiential foundation for the reality of interdependent non-dual wholeness. In order to advance Bey’s critique of ‘the sleep of Order’, pathological (calculative) reason, and Western technological development, his work is brought into dialogue with that of schizoanalyst and philosopher Felix Guattari. The final part of this paper discusses the implications of Bey’s Immediatist project for contemporary artistic practice, with special emphasis placed on musical forms and the possibility of reviving Occidental sacred musical traditions. KEYWORDS: Hakim Bey, Peter Lamborn Wilson, Felix Guattari, Chaos, Nothing, Ontological Anarchy